2008
DOI: 10.1590/s1516-89132008000500010
|View full text |Cite
|
Sign up to set email alerts
|

Jurema-Preta (Mimosa tenuiflora [Willd.] Poir.): a review of its traditional use, phytochemistry and pharmacology

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 14 publications
(16 reference statements)
0
34
0
5
Order By: Relevance
“…(MAIA, 2004). Furthermore, it is used for medicinal purposes against various diseases (SOUZA et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(MAIA, 2004). Furthermore, it is used for medicinal purposes against various diseases (SOUZA et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It contains information about the main psychoactive substances, the mode of action and side effects after use of plant materials. THH, harmaline, harmine [15,47] MAOI, facilitates DMT effects [46] convulsions, difficulty breathing, laxative, trembling, lower heart rate, paralysis, strong hallucinations, dizziness, nausea, vomiting…”
Section: Designer Drugs In Polandmentioning
confidence: 99%
“…Mimosa hostilis, Mimosaceae) naturally grows in North part of South America and in Mexico. It has been traditionally used by the Brazilian Indians for curing infections, inflammations against bronchitis, coughs, headache, external ulcers and also for divination [47,48]. Pharmacological studies showed that M .…”
Section: Illegal Plant Species Descriptionmentioning
confidence: 99%
“…Os extratos de M. tenuiflora e M. hostilis, que segundo a GRIN (2010) são sinônimos, têm demostrado atividade antimicrobiana contra uma série de patógenos (Souza et al, 2008;Borges et al, 2013) além de apresentar atividade antioxidante, cicatrizante, anti-inflamatória (Cruz, 2013) gloeosporioides (Sousa et al, 2012 …”
Section: Introductionunclassified